Membrane shedding in kidney (MDCK) cells as revealed by covalent markers during quantification of endocytosis and transcytosis - Godenir, Nicole (Division of Medical Biochemistry and Structural Biology, 2018)
Membrane traffic in polarised cells was investigated by growing Madin-Darby canine kidney (MOCK) cells on ·permeable polycarbonate filter supports which allowed access to both sides of the cell monolayer. Membrane glycoconjugates on the apical and basolateral cell surfaces were labelled enzymatically with ³H- and ¹⁴C-galactose, respectively, to provide covalent membrane markers. Experiments were done to quantitate membrane traffic during endocytosis at the respective plasma membrane domains and that due to transcytosis. Internalized label was quantitatively distinguished from label on the respective cell surface by its resistance to removal by glycosidases.